Limnological profile of Kamal Sagar Wetland of Burdwan Town, West Bengal, India - BADSHA, S.K. ALAMGIR; JANA, N.C. (Nusantara Bioscience, 2017)
Badsha SKA, Jana NC. 2017. Limnological profile of Kamal Sagar Wetland of Burdwan Town, West Bengal, India. Nusantara Bioscience 9: 195-201. Wetlands, valuable ecosystems that occur extensively throughout the world in all climatic zones, are estimated to cover about 6% of the earth surface. The Kamal Sagar Wetland (KASW) is one of the important perennial wetlands of Burdwan, India. The documentary, field survey with questionnaires and laboratory analysis methods have been used from 2009 to 2013 to access to information, for identifying capabilities and limiting factors of the Wetland. It’s physical, chemical and biological parameters have been considered to know the potentialities of wetlands. The results are showing that BOD5 is high in pre-monsoon season for the presence of hydrocarbon of automobile shops and garbage mixing by the stakeholders. pH is alkaline in all time. Transparency & euphotic limit values are half in summer season than other seasons because of low water depth, turbidity ranges from 60 to 75 NTU, organic carbon ranges from 0.55% to 0.79%. Surface runoff, hydrocarbon, and development activities of Burdwan Town have increased pollution load in this Wetland. It can be considered as important threats for the wetland. It is recommended to make a necessary study on physicochemical and biological parameters of wetland and also the current threats and opportunities.
Keywords: Capability; ecology; limiting factors; sustainability